Analysis for Science Librarians of the 2015 Nobel Prize in Physiology or Medicine: The Life and Work of William C. Campbell, Satoshi Ōmura, and Youyou Tu. Issue 1 (2nd January 2016) - Gilman, Neyda V.
ABSTRACT: Parasites affect humans worldwide with varying degrees of seriousness. Some of the most impactful parasitic infections affect millions of people, many of whom are already impoverished and struggling. The discoveries of the 2015 Nobel Laureates in Physiology of Medicine have changed the way some of these serious parasitic infections are treated, saving and improving the lives of countless people. These Laureates are William C. Campbell, Satoshi Ōmura, and Youyou Tu.